Analysis of Bacteria Community in the sediment from Bangka Island, North Sulawesi - Meivyarni Wangka; Stenly Wullur; Esther Angkouw; Jane Mamuaja; Reiny Tumbol; Elvy Like Ginting (Jurnal Ilmiah PLATAX, 2020)
Marine sediments are nutrient-rich and is a suitable habitat of bacteria. This research is a preliminary study of molecular analysis to identify the bacteria in the sediments from the littoral area that covered by mangroves in Bangka Island, North Sulawesi. The purposes of this study are to obtain the uncultivated bacterial DNA genome  which is used to identify the bacteria  and  bacterial community  in the sediments. Isolation of DNA genome from uncultured bacterial was carried out by following the genomic DNA extraction procedure using the DNeasy® PowerSoil Extraction Kit. Before isolating the bacterial DNA, sample were went through freezing and thawing processes. The DNA isolation result was subsequently tested using electrophoresis and UV-Vis spectrophotometers. Subsequently the genomic DNA was amplified using Polymerase Chain Reaction and the bacteria were identified using Next Generation Sequencing (NGS) analysis. The results of this study showed that the DNA of uncultured bacteria from sediment have the purity of 1.05 and the DNA amplification band was detected at 1300-1600bp. The bacteria in Bangka Island, North Sulawesi sediments were consisted of Gemmatimonadetes, Acidobacteria, Chioroflexi, Firmicutes, Bacteroidetes, Actinobacteria, Cyanobacteria and Proteobacteria respectively. Phylum Proteobacteria was found has the highest relative abundance  in the sediment.Keywords : Bacteria, Deoxyribo Nucleic Acid, Sediment, Uncultured. ABSTRAKSedimen laut merupakan suatu habitat yang kaya akan nutrient dan merupakan habitat dari bakteri. Penelitian ini merupakan tahapan awal dalam rangkaian analisis molekuler bakteri yang hidup di sedimen dari daerah litoral yang ditumbuhi oleh mangrove pada Pulau Bangka Sulawesi Utara. Tujuan penelitian ini adalah untuk mendapatkan DNA genom bakteri tanpa kultivasi yang digunakan dalam analisis jenis dan komunitas bakteri pada sedimen. Isolasi DNA genom bakteri tanpa kultivasi dilakukan dengan mengikuti prosedur Kit ekstraksi DNA DNeasy® PowerSoil. Sebelum tahap isolasi DNA bakteri, sampel diperlakukan proses freezing and thawing. Hasil isolasi DNA diuji menggunakan elektroforesis dan spektrofotometer UV-Vis. DNA genom diamplifikasi menggunakan Polymerase Chain Reaction dan ditentukan jenis bakteri dengan menggunakan Next Generation Sequencing analysis. Hasil penelitian menujukkan bahwa DNA bakteri tanpa kultivasi  memiliki kemurnian 1,05. DNA amplifikasi terdeteksi pada posisi 1300-1600bp. Dan jenis bakteri yang hidup pada sedimen di Pulau Bangka Sulawesi Utara, terdiri dari filum Gemmatimonadetes, Acidobacteria, Chioroflexi, Firmicutes, Bacteroidetes, Actinobacteria, Cyanobacteria dan Proteobacteria. Kelimpahan tertinggi bakteri yang hidup pada sedimen tersebut adalah  filum Proteobacteria.Kata kunci : Bakteri, Deoxyribo Nucleic Acid, Sedimen, Tanpa kultivasi.